Beneficial Effects of Low-Dose Intravenous Dexmedetomidine Premedication in Patient Undergoing Laparoscopic Cholecystectomy Under General Anesthesia: A Prospective, Double-Blind, Randomized Controlled Trial - Zheng L; Fang T; Zhang W; Zhang X; Ren Z; Qin W; Liang W; Ma Q; Yin N (Dove Medical Press, 2024)
Longbin Zheng,1,* Tao Fang,2,* Wei Zhang,1 Xiaojing Zhang,1 Zhiqiang Ren,1 Weimin Qin,1 Wenbo Liang,1 Qing Ma,1 Ning Yin1 1Department of Anesthesiology, Sir Run Run Hospital, Nanjing Medical University, Nanjing, Jiangsu Province, People's Republic of China; 2Department of Anesthesiology, Xinchang County People's Hospital, Xinchang, Zhejiang Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Ning Yin, Department of Anesthesiology, Sir Run Run Hospital, Nanjing Medical University, No. 109 Longmian Avenue, Nanjing, Jiangsu Province, 211112, People's Republic of China, Email yinning882000@126.comPurpose: Dexmedetomidine (Dex) is a potent and highly selective α 2-adrenergic receptor agonist. Within an appropriate dose range, Dex can effectively attenuate the surgical stress response, provide intraoperative hemodynamic stability, and improve the patient recovery quality. High-dose Dex can delay patient awakening from anesthesia and increase the incidence of bradycardia. This randomized controlled trial aimed to investigate the effects of low-dose intravenous Dex premedication in patients undergoing laparoscopic cholecystectomy (LC).Material and Methods: In total, 100 patients undergoing LC were equally randomized into Group C (premedication with saline) and Group D (premedication with 0.5 μg/kg Dex). The patients were premedicated with saline or Dex, depending on the group, before anesthesia induction. Following this, anesthesia induction and endotracheal intubation was performed, and anesthesia was maintained during surgery. Following the completion of the surgery, the patients were transferred the post-anesthesia care unit (PACU) and stayed there until they met the PACU discharge criteria. The hemodynamic parameters, consumption of anesthetics, surgical duration, postoperative awakening time, extubation time, postoperative pain, and complications were recorded.Results: No significant differences were observed in the heart rate (HR) and mean arterial pressure (MAP) between the two groups before premedication (P> 0.05). The MAP and HR immediately after endotracheal intubation and immediately after extubation were significantly lower in Group D than in Group C (P< 0.05 for both). The incidence of bradycardia was significantly higher in Group D than in Group C (P< 0.05), while atropine was used in neither group. Propofol and remifentanil consumption was significantly lower in Group D than in Group C (P< 0.05). The postoperative awakening and extubation times were significantly shorter in Group D than in Group C (P< 0.05). The postoperative visual analog scale scores for pain and incidence of nausea, vomiting, and cough were significantly lower in Group D than in Group C (P< 0.05 for all).Conclusion: Our data suggest that premedication with dexmedetomidine (0.5 μg/kg) before general anesthesia induction can effectively attenuate intraoperative stress response and postoperative pain, maintain perioperative hemodynamic stability, and decrease the incidence of adverse events, which might be an effective and safe anesthetic protocol during LC worthy of further clinical application.Keywords: dexmedetomidine, laparoscopic cholecystectomy, general anesthesia, premedication